2002
DOI: 10.1021/jp020863+
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of the Biotin−Avidin Bond-Rupture Force Studied by Atomic Force Microscopy

Abstract: We report for the first time an atomic force microscopy (AFM) investigation of the dependence of unbinding force on temperature at controlled loading rate. AFM force measurements of biotin-avidin interactions were acquired at various temperatures ranging from 13 to 37°C using force loading rates that are slow enough to ignore dissipative friction and to assume thermal equilibrium. With our established Poisson statistical analysis method, the unbinding force at a fixed loading rate between an individual biotin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 26 publications
0
42
0
Order By: Relevance
“…Lo et al [1139] have studied also the temperature dependence of the biotin-avidin specific force rupture. AFM force measurements have been performed at various temperatures (13-37 8C) with slow constant loading rates.…”
Section: Rupture Force Of Specific Interactionsmentioning
confidence: 99%
“…Lo et al [1139] have studied also the temperature dependence of the biotin-avidin specific force rupture. AFM force measurements have been performed at various temperatures (13-37 8C) with slow constant loading rates.…”
Section: Rupture Force Of Specific Interactionsmentioning
confidence: 99%
“…This allows for the detection of the unbinding force (the maximum force at the moment of receptor-ligand detachment), which is obtained upon retraction of the cantilever from the surface. Recently, unbinding forces were quantified for various receptor-ligand pairs, including biotin-avidin [113], DNA bases [114], antibody-antigen [115][116][117], and cell-tocell recognition proteins [118][119][120]. It was also shown that the value of the unbinding force for a certain receptor-ligand pair is not unique but rather is dependent on the dynamics of the experiment [113,[121][122][123].…”
Section: Receptor-ligand Recognition Imaging By Afmmentioning
confidence: 99%
“…Linkage of nanoparticles to MTs shuttles was accomplished using biotin-streptavidin, forming a relatively strong, but non-covalent bond between components. 39 Nanoparticles were assembled on MTs that were bound to surface-tethered kinesin in order to avoid inhibition of transport as previously reported, 29 by localizing the attached cargo to the top and sides of the MT shuttles. The density of nanoparticles attached to MTs was the most significant factor affecting kinesin transport, and can be regulated by controlling the frequency of biotinylated tubulin, and/or the concentration of nanoparticles used for attachment.…”
Section: Discussionmentioning
confidence: 99%